The co-occurrence of substance misuse, domestic abuse, and child maltreatment: Can Family Drug and Alcohol Courts play a part? - Harwin, Judith; Barlow, Charlotte (Frontiers in Psychiatry, 2022)
This review article focuses on the inter-relationship between substance misuse, domestic abuse, and child maltreatment, especially in the context of care (child protection) proceedings. It reviews what is known about the prevalence and impact of co-occurring domestic abuse and substance misuse on adult and child victims, and the response of criminal and family law and intervention programmes in supporting families to address these problems holistically. Special attention is paid to the role of Family Drug and Alcohol Courts (FDACs), a radical problem-solving approach to care proceedings, which provide integrated interventions to the range of co-occurring problems that trigger the proceedings. Despite clear evidence of the greater harm to children when exposed to these two parental difficulties, the review has found a lack of systematic information on the prevalence of co-occurrence and a lack of effective integrated interventions, including within care proceedings. It argues that the FDAC approach is well suited to respond to co-occurring substance misuse and domestic abuse in care proceedings and it has the potential to break down silos across sectors. However, in the absence of empirical evidence, this premise would need testing. A particular focus of the review has been on efforts to overcome silos in practice, law and policy. Promising initiatives are described in criminal and family law to improve the response to domestic abuse that build on the Domestic Abuse Act 2021, the first dedicated domestic abuse legislation in England and Wales. All of them are based on problem-solving approaches used in other jurisdictions. Despite these initiatives, the review concludes that there remain significant barriers to effectively align law, policy and practice to ensure that domestic abuse strategy recognizes and responds to the overlaps with substance misuse.